Mutual versus Stock Insurers: Fair Premium, Capital, and Solvency - Christian Laux; Alexander Muermann (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
Mutual insurance companies and stock insurance companies are different forms of organized risk sharing: policyholders and owners are two distinct groups in a stock insurer, while they are one and the same in a mutual. This distinction is relevant to raising capital, selling policies, and sharing risk in the presence of financial distress. Up-front capital is necessary for a stock insurer to offer insurance at a fair premium, but not for a mutual. In the presence of an owner-manager conflict, holding capital is costly. Free-rider and commitment problems limit the degree of capitalization that a stock insurer can obtain. The mutual form, by tying sales of policies to the provision of capital, can overcome these problems at the potential cost of less diversified owners.
Keywords: G22; G32; 330; ownership structure; insurance; owner-manager conflict; capital; default; Versicherung; Privatversicherung; Eigentümerstruktur; Versicherungsprämie; Eigenkapital; Betriebliche Liquidität; Theorie